Escapes from religious oppression - Currie, Stephen, 1960- (San Diego, Calif. : Lucent Books, 2004)
Describes five escapes from religious oppression, from three continents in three centuries, of individuals or groups representing five different faiths who were willing to risk everything they had for the chance to worship freely.
Includes bibliographical references (p. 103-106) and index.
Keywords: Freedom of religion -- Biography -- Juvenile literature; Human rights -- Biography -- Juvenile literature; Persecution -- Biography -- Juvenile literature; Religious tolerance -- Biography -- Juvenile literature